Structural and functional changes in the brains of patients with Rett syndrome: A multimodal MRI study - Takeguchi, Ryo; Kuroda, Mami; Tanaka, Ryosuke; Suzuki, Nao; Akaba, Yuichi; Tsujimura, Keita; Itoh, Masayuki; Takahashi, Satoru (Journal of the neurological sciences, 2022)
To clarify the relationship between structural and functional changes in the brains of patients with Rett syndrome (RTT) using multimodal magnetic resonance imaging (MRI). Nine subjects with typical RTT (RTTs) and an equal number of healthy controls (HCs) underwent structural MRI, diffusion tensor imaging (DTI), and resting-state functional MRI (rs-fMRI). The measurements obtained from each modality were statistically compared between RTTs and HCs and examined for their correlation with the clinical severity of RTTs. Structural MRI imaging revealed volume reductions in most cortical and subcortical regions of the brain. Remarkable volume reductions were observed in the frontal and parietal lobes, cerebellum, and subcortical regions including the putamen, hippocampus, and corpus callosum. DTI analysis revealed decreased white matter integrity in broad regions of the brain. Fractional anisotropy values were greatly decreased in the superior longitudinal fasciculus, corpus callosum, and middle cerebellar peduncle. Rs-fMRI analysis showed decreased functional connectivity in the interhemispheric dorsal attention network, and between the visual and cerebellar networks. The clinical severity of RTTs correlated with the volume reduction of the frontal lobe and cerebellum, and with changes in DTI indices in the fronto-occipital fasciculus, corpus callosum, and cerebellar peduncles. Regional volume and white matter integrity of RTT brains were reduced in broad areas, while most functional connections remained intact. Notably, two functional connectivities, between cerebral hemispheres and between the cerebrum and cerebellum, were decreased in RTT brains, which may reflect the structural changes in these brain regions. [Display omitted] •Rett syndrome (RTT) brains were examined using multimodal MRI techniques.•Reduced interhemispheric and cerebro-cerebellar connections were noted.•Clinical severity of RTT patients correlated with the altered connections.•These alterations may underlie the functional changes in RTT brains.